Training on Preparing Financial Reports Using Accurate Software for MSMEs - Erna Hendrawati; Khoirul Abidin; Mira Pramudianti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The purpose of implementing this service is to provide literacy to MSMEs about financial reports, train and assist MSMEs in Sememi village, Benowo district in the use of Accurate softwarw for menyusun financial statements.The stages of service implementation consist of: planning, implementing and mentoring stages. This training and mentoring activity can be said to be successful because participants argue that this training and mentoring is very useful for providing understanding about reports. financial. This service can also be a provision for MSMEs to compile financial reports with Accurate software.